the Perlindungan Privasi dan Data Pribadi Konsumen Pada Online Marketplace Qualitva.id: Protection of Consumer Privacy and Personal Data on the Qualitva.id Online Marketplace - M Guntur Guntur (Jurnal Ilmu Komputer dan Sistem Informasi |JIKSI|, 2022)
The online market system is one form of development in e-commerce activities. The online market system provides facilities for shopping online with various services aimed at making it easier for online consumers or e-consumers. However, on the other hand, services that make this easier also carry potential threats to personal data and online consumer privacy. This research focuses on discussing personal data protection and privacy for e-consumers in online market systems, using normative or legal research methods. The research approaches used include the Statute Approach, Conceptual Approach, Case Approach, and Comparative Approach. The research results show that the development of e-commerce in Indonesia has experienced rapid progress, supported by state initiatives such as the "1000 technopreneur" program and other programs that support the birth of new start-ups. However, to operate effectively, adequate legal protection, especially regarding consumer privacy rights, is a necessity. Within the national regulatory framework, there are laws such as Law Number 11 of 2008 concerning ITE and PP Number 28 of 2012 concerning the Implementation of Electronic Systems and Transactions. With this regulation, the Ministry of Communication and Information (Kemenkominfo) can register and collect data on e-commerce business actors. This process involves profiling and database reports to prevent consumers from potential fraud that may be carried out by irresponsible parties.